1998
DOI: 10.1007/s11661-998-0226-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical property and fracture behavior of squeeze-cast Mg matrix composites

Abstract: The present study aims to investigate the microstructure and fracture properties of AZ91 Mg matrix composites fabricated by the squeeze-casting technique, with variations in the reinforcement material and applied pressure. Microstructural and fractographic observations, along with in situ fracture tests, were conducted on three different Mg matrix composites to identify the microfracture process. Two of them are reinforced with two different short fibers and the other is a whisker-reinforced composite. From th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…This test has shortcomings, such as introduction of a sharp notch instead of a fatigued precrack and thin specimen thickness, which does not satisfy the plane strain condition. It was reported that the toughness measured under the plane strain condition was similar to that measured under the plane stress condition for brittle materials, [20] and that the apparent fracture toughness obtained from the sharp-notch-inserted CT specimen was similar to that of the fatigued-crackinserted specimen. [21] Thus, the apparent fracture toughness of the surface composites could be evaluated reliably and comparatively.…”
Section: Methodsmentioning
confidence: 59%
See 1 more Smart Citation
“…This test has shortcomings, such as introduction of a sharp notch instead of a fatigued precrack and thin specimen thickness, which does not satisfy the plane strain condition. It was reported that the toughness measured under the plane strain condition was similar to that measured under the plane stress condition for brittle materials, [20] and that the apparent fracture toughness obtained from the sharp-notch-inserted CT specimen was similar to that of the fatigued-crackinserted specimen. [21] Thus, the apparent fracture toughness of the surface composites could be evaluated reliably and comparatively.…”
Section: Methodsmentioning
confidence: 59%
“…In brittle materials such as surface composites, however, the fracture toughness measured under the plane stress condition does not deviate much from that measured under the plane strain condition. [20] Thus, the apparent values measured from this method can be used to evaluate the fracture toughness reliably on the comparative basis.…”
Section: Apparent Fracture Toughnessmentioning
confidence: 99%
“…In general, two different methods have been extensively used. The first basically included the Eshelby or "mean stress" theory, 6) which treats the strengthening of composites reinforced with elastic ellipsoidal inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In order to facilitate the development and design of whisker reinforced composites, constitutive relationships must be developed that predict their effective elastic modulus and overall stressstrain response. Although some analytical and semi analytical models have been developed to evaluate the effective material properties of fiber and particle reinforced composites based on homogenization techniques, [4][5][6] they have not been able to be extended to composites with irregular reinforcement geometries and complex microstructures.…”
Section: Introductionmentioning
confidence: 99%